Search for invisible Higgs boson decays in vector boson fusion at s=13TeV with the ATLAS detector - Santos, S. P. Amor dos (2019)
We report a search for Higgs bosons that are produced via vector boson fusion and subsequently decay into invisible particles. The experimental signature is an energetic jet pair with invariant mass of O(1) TeVand O(100) GeVmissing transverse momentum. The analysis uses 36.1fb−1of ppcollision data at √s=13 TeVrecorded by the ATLAS detector at the LHC. In the signal region the 2252observed events are consistent with the background estimation. Assuming a 125 GeVscalar particle with Standard Model cross sections, the upper limit on the branching fraction of the Higgs boson decay into invisible particles is 0.37at 95%confidence level where 0.28was expected. This limit is interpreted in Higgs portal models to set bounds on thewimp–nucleon scattering cross section. We also consider invisible decays of additional scalar bosons with masses up to 3 TeVfor which the upper limits on the cross section times branching fraction are in the range of 0.3–1.7 pb.